Negras, velhas, pessoas idosas, experientes e estudantes: um estudo antropológico das vivências e resistências na Universidade Aberta à Terceira Idade no Brasil - Santana, Lisianne Lima de (2023)
This dissertation aims to understand the intersection between old age, racism and education from the narratives of experiences and resistance of old black women, elderly people, experienced people, students of Universities Open to the Third Age in Brazil. In the first chapter “Aging in Brazil”, demographic data on aging in Brazil, legislation related to old age, discussion on the term old, elderly and third age will be presented. In the second, “Education and Open University for the Elderly”, the origin of the University open to the Elderly and its development over the years in the world is contextualized. And in the third chapter, the “narratives of the experiences of students 60+ in specific educational contexts are shared.Thus, I present this research through netnography. According to Amaral et al (2009, p.34),they understand that netnography is not a mere transposition “from the ethnographic method to media environments and online relationships through monitoring of social actors” andmention “the communicational dynamics both between the observed objects and in theresearcher-object relationship may differ mainly in relation to the notion of time-space.